METHODS AND PROCEDURES FOR GATHERING AUDIT EVIDENCE: ESSENCE AND PECULIARITIES OF APPLICATION - STOIKA, Natalia; STOIKA, Myroslav; NOVICHENKO, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article examines the necessity and specific features of selecting and applying various methods and audit procedures during a financial statement audit. It is emphasized that the diversity of methods is crucial for obtaining sufficient and appropriate audit evidence. It is established that the effective selection of methods for conducting an audit allows for the detection of inconsistencies, misstatements, errors, and instances of fraud in accounting and financial reporting, which forms the basis for the auditor’s well-grounded opinion. The article discusses the four main stages of an audit (organizational, preparatory, methodical, resulting) and the audit work performed at each of these stages. The essence of the concept "method" is examined, and a two-level classification of methods is presented: general (universal, unformalized) and special (methods of specific sciences). A list and characteristics of general methods actively used by auditors to gather audit evidence are provided (specifically, observation, comparison, measurement, experiment, analysis, synthesis, generalization, interview, and questionnaire). It is determined that these empirical methods are based on the auditor’s experience and help to confirm or refute the assumptions made. The directions for applying special methods in audit practice are identified, which include analytical procedures (financial, functional-cost analysis), statistical methods (e.g., sampling method), and methods of mathematical analysis (for assessing the dynamics of indicators, cost optimization, and calculating the present value of cash flows). It is established that the selection and application of various general and special methods in auditing are used for conducting audit procedures with the aim of obtaining audit evidence. The selection of various methods depends on the experience and competence of the auditor.